The Effect of Managerial Overconfidence on Abnormal Audit Fees with Respect to Stakeholder Equity Mechanisms - Esmaeil Akhlaghi Yazdinejad; Hossein Nourani (Iranian Journal of Accounting, Auditing & Finance)
The pricing of audit services has been a topic of interest to many audit researchers. In case auditors recognize managerial overconfidence, they are expected to incorporate this risk factor into their audit planning and compensate for additional audit efforts to reduce diagnostic risk. This research investigates the effect of the stakeholder equity mechanisms on the relationship between managerial overconfidence and abnormal audit fees. The research sample comprises 144 listed firms on the Tehran Stock Exchange (TSE) from 2012 to 2021. Multiple regression techniques are used to test hypotheses. Furthermore, the Burks et al. (2019) method of testing interaction role is applied. The capital expenditure ratio index has been used for measuring managerial overconfidence. The results indicated a positive and significant relationship between managerial overconfidence and abnormal fees for auditing services. Moreover, the stakeholder equity mechanisms undermine the relationship between managerial overconfidence and abnormal fee for auditing services.